2021
DOI: 10.1002/fsn3.2589
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and associated factors of aflatoxin M1 in raw cow milk in South Gondar Zone, North West Ethiopia, 2020

Abstract: Aflatoxin M1 is the most significant toxin of milk and milk products. It is immunosuppressive, mutagenic, and carcinogenic compounds to humans. Therefore, this study was aimed to evaluate the concentration of aflatoxin M1 and its determinants in raw cow milk sample intended for human consumption in South Gondar Zone, Ethiopia.A cross-sectional study was conducted on a total of 100 dairy farmers from January to February 2020. Around 50 ml, 100 raw milk samples were collected for aflatoxin M1 analysis. A simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…When we measure it against the Ethiopian standard, the AFM1 concentration in pasteurized milk (0.5%) exceeds it by a significant 247.4%. Other studies conducted in Ethiopia have reported varying prevalence rates, such as 41% in Gondar [34], 68% in the Gurage zone [35], and 67.20% across three regions of Ethiopia [36]. Furthermore, the percentage of AFM1 found in milk from the milksheds in Addis Ababa was even higher than our findings, reaching 100% in all samples tested.…”
Section: Discussioncontrasting
confidence: 75%
“…When we measure it against the Ethiopian standard, the AFM1 concentration in pasteurized milk (0.5%) exceeds it by a significant 247.4%. Other studies conducted in Ethiopia have reported varying prevalence rates, such as 41% in Gondar [34], 68% in the Gurage zone [35], and 67.20% across three regions of Ethiopia [36]. Furthermore, the percentage of AFM1 found in milk from the milksheds in Addis Ababa was even higher than our findings, reaching 100% in all samples tested.…”
Section: Discussioncontrasting
confidence: 75%
“…However, there is a scarcity of studies regarding AFM 1 occurrence in dairy products in Ethiopia. Thus far, only three have been published [15][16][17]. These investigations reported the presence of AFM 1 occurrence in milk and cottage cheese in particular district areas.…”
Section: Introductionmentioning
confidence: 99%
“…In Tanzania, contaminated maize consumption was a main cause of AF exposure in children aged 24-36 months associated with breastfeeding and weaning foods [49]. In Ethiopia, maize and raw cow's milk from different places and agro-ecological zones were contaminated by high levels of AF and confirmed as a serious threat to smallholder farmers [47,50]. However, the investigation of AF contamination of crops in Ethiopia is poorly regulated.…”
Section: Discussionmentioning
confidence: 99%